2004
DOI: 10.3354/dao061041
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of mycobacteria from striped bass Morone saxatilis from the Chesapeake Bay

Abstract: Mycobacteriosis in striped bass Morone saxatilis of Chesapeake Bay, USA, was first diagnosed in 1997 based on the presence of granulomatous inflammation and acid-fast bacteria in skin and spleen. To confirm histopathology, bacteriological detection and identification of mycobacteria were begun using splenic tissue from fish with and without skin ulcerations. On the basis of initial studies using a variety of selective and nonselective media, decontamination, homogenization and incubation conditions, a simple a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
96
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(102 citation statements)
references
References 35 publications
4
96
2
Order By: Relevance
“…The 3 species of Mycobacterium traditionally associated with infections in fishes are M. marinum, M. chelonae and M. fortuitum (Gauthier & Rhodes 2009), and reports continue to implicate these species in fish disease worldwide. It was therefore surprising when bacteriological surveys of Chesapeake Bay striped bass conducted from 1997 to 2001 indicated that M. marinum comprised only about 3% of Chesapeake Bay striped bass isolates, and neither M. chelonae nor M. fortuitum was detected (Rhodes et al 2004). Since this first report, M. chelonae has been isolated from only a single striped bass in Delaware Bay (Ottinger et al 2007), and M. fortuitum has not yet been isolated from internal tissues of this fish.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The 3 species of Mycobacterium traditionally associated with infections in fishes are M. marinum, M. chelonae and M. fortuitum (Gauthier & Rhodes 2009), and reports continue to implicate these species in fish disease worldwide. It was therefore surprising when bacteriological surveys of Chesapeake Bay striped bass conducted from 1997 to 2001 indicated that M. marinum comprised only about 3% of Chesapeake Bay striped bass isolates, and neither M. chelonae nor M. fortuitum was detected (Rhodes et al 2004). Since this first report, M. chelonae has been isolated from only a single striped bass in Delaware Bay (Ottinger et al 2007), and M. fortuitum has not yet been isolated from internal tissues of this fish.…”
Section: Introductionmentioning
confidence: 99%
“…Fish were placed on ice immediately and necropsy was performed within 24 h after collection. Bacterial isolation and phenotypic characterization were as described in previous work (Rhodes et al 2004, Gauthier et al 2008b. Briefly, 0.1 to 0.5 g of spleen was homogenized using a Tenbroek tissue grinder, and dilutions were made in Butterfield's buffer + 0.05% Tween-80.…”
Section: Fish Collections and Bacterial Isolation Striped Bassmentioning
confidence: 99%
See 2 more Smart Citations
“…Primary isolation is commonly made using Lowenstein and Middlebrook media (BD Difco). Rhodes et al (2004) developed a tissue preparation and media inoculation procedure that enhances the recovery of Mycobacterium spp. from fish (i.e., striped bass M. saxatilis) using Middlebrook 7H9 medium supplemented with antimicrobials (Teska et al, 1997) to reduce overgrowth by contaminants and thereby increase recovery of the pathogen.…”
Section: Less Common Fish Bacterial Pathogensmentioning
confidence: 99%